Tricyclic and selective serotonin-reuptake-inhibitor antidepressants compared with placebo in randomized trials for acute major depression - Undurraga, Juan; Baldessarini, Ross J. (Journal of Psychopharmacology, 2017)
This letter discusses the efficacy of tricyclic and selective serotonin-reuptake-inhibitor antidepressants compared with placebo in randomized trials for acute major depression. A direct comparison between two active drugs does not necessarily mean that they are efficacious. If a placebo arm is absent, it is not possible to rule out a similar lack of efficacy between active treatment. To address this question, the authors selected the trials that compared TCAs versus SSRIs versus placebo, and compared their efficacy based on random-effects meta-analyses. The pooled efficacy of both SSRIs and TCAs was highly superior to placebo treatment. Moreover, their effects were very similar and did not differ significantly. These findings add to the impression that these two major classes of antidepressant drugs have similar average efficacy in acute major depression, and that their similarity is not likely to represent false negative findings arising from a high proportion of negative trials in which both types of agents were ineffective. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: Clinical Trials; Major Depression; Placebo; Serotonin Reuptake Inhibitors; Tricyclic Antidepressant Drugs; major depression; placebo; randomized trials; selective serotonin-reuptake-inhibitors; tricyclic antidepressants